Penyiapan Media Tanam Untuk Budidaya Tanaman Sayuran Pada Lahan Gambut Di Kecamatan Pontianak Utara - Suswati, Denah; Dolorosa, Eva; M, Leony Agustine (Lembaga Dongan Dosen, 2023)
This activity aims to provide solutions to the problems faced by the Dharmaputra Farmers Group on Jl. Budi Utomo, Gg. Dharmaputra1, North Pontianak District, who wants a change in cultivating vegetable crops on peatlands that is more profitable and environmentally friendly through the application of more efficient technology, so that it is hoped that farmer groups can prepare planting media for cultivating vegetable crops. The problems faced by farmer groups are: 1) The productivity of vegetable crops is still relatively low, 2) They do not yet understand how to apply environmentally friendly vegetable cultivation technology by utilizing agricultural waste, 3) The PKM implementing team provides solutions to existing problems, namely through several methods include: 1) Providing training in preparing planting media that is environmentally friendly and can increase soil fertility 2) Providing training in making organic fertilizer using agricultural waste 3) Exposure to technology for cultivating vegetable crops on peatlands. The implementation of PKM is carried out through counseling, demonstrations and direct training regarding the preparation of planting media for cultivating vegetable plants on peatlands with organic fertilizer processing, evaluation and monitoring of activities that have been carried out, and reporting